ATIM-16. PHASE 1 STUDY RESULTS OF M7824 (MSB0011359C), A BIFUNCTIONAL FUSION PROTEIN TARGETING TGF- AND PD-L1, AMONG PATIENTS WITH RECURRENT GLIOBLASTOMA (rGBM). (5th November 2018) - Khasraw, Mustafa; Weller, Michael; Estelles, David Lorente; Kolibaba, Kathryn; Lee, Chee; Gedye, Craig; De La Fuente, Macarena; Vicente, David; Reardon, David; Ojalvo, Laureen; Helwig, Christoph; Gourmelon, Carole; et al.
Abstract: BACKGROUND: TGF- signaling promotes tumor immunosuppression; TGF- inhibition in the tumor microenvironment may enhance the response to antiPD-L1 treatment. M7824 is an innovative, first-in-class, bifunctional fusion protein composed of a human antiPD-L1 IgG1 monoclonal antibody fused with two extracellular domains of TGF RII to function as a TGF- trap. We report safety and efficacy of M7824 in patients with rGBM. METHODS: In this efficacy expansion cohort of the ongoing, phase 1 trial NCT02517398, patients with rGBM who progressed after chemoradiation received M7824 1200 mg q2w until disease progression, unacceptable toxicity, or trial withdrawal. The primary objective was disease control rate (DCR) per RANO; secondary objectives included safety/tolerability. RESULTS: Among 35 patients, median age was 57 years, 68.6% were male, and 91.4% were at first recurrence. At 15 months minimum follow-up, median treatment duration was 8.1 (range, 2.0–72.1) weeks; four patients remained on treatment at >1 year, and one additional patient decided to stop treatment per protocol at 12 months. Two patients had a partial response, and nine had stable disease (DCR, 31.4% [95% CI, 16.9–49.3]), of which two exhibited early progressive disease and subsequent durable stable disease ongoing for >12 months per investigators assessment. The most common treatment-related adverse events (TRAEs) were gingival bleeding (17.1%), asthenia (14.3%), pruritus, and rash (each 11.4%). Grade 3 TRAEs (6 patients, 17.1%) included diarrhea, eczema, increased liver/pancreatic enzymes, papular rash, papules, one grade 4 asymptomatic increased lipase, and one grade 5 intratumoral hemorrhage (investigator-assessed) coterminous with disease progression. CONCLUSIONS: M7824 demonstrated a manageable safety profile and encouraging efficacy in rGBM, including two durable partial responses and a DCR of 31.4%. Further investigation of M7824 in GBM is warranted; future development aims to define molecular characteristics of responders.